Measurement of the Z boson differential production cross section using its invisible decay mode (Z -> nu(nu)over-bar) in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2021)
Measurements of the total and differential fiducial cross sections for the Z boson decaying into two neutrinos are presented at the LHC in proton-proton collisions at a center-of-mass energy of 13TeV. The data were collected by the CMS detector in 2016 and correspond to an integrated luminosity of 35.9 fb(-1). In these measurements, events are selected containing an imbalance in transverse momentum and one or more energetic jets. The fiducial differential cross section is measured as a function of the Z boson transverse momentum. The results are combined with a previous measurement of charged-lepton decays of the Z boson. The measured total fiducial cross section for events with Z boson transverse momentum greater than 200 GeV is 3000(-170)(+180) fb.
Keywords: Hadron-Hadron scattering (experiments); Lepton production; Particle and resonance production; ELECTROWEAK CORRECTIONS; HADRONIC PRODUCTION